Creative Adaptive Physical Activities as Therapeutic Media for Motor Development in Children With Autism - Syfah Nur Kaffah; Habibi Hadi Wijaya; Qory Armen Gemael (Media Ilmu Keolahragaan Indonesia, 2024)
Children with autism often experience significant challenges in gross motor development due to sensory-motor limitations and neurological impairments, which hinder their participation in physical and social environments. Existing interventions for motor enhancement in special-needs populations frequently lack personalization and continuity in application. The present study aims to evaluate the effectiveness of creative adaptive physical activities in improving gross motor skills in autistic children by implementing a structured and repetitive intervention. Employing a quantitative approach through a Single Subject Research (SSR) design with A-B-A phases, the study analyzed changes in motor performance across baseline, intervention, and post-intervention phases. One participant diagnosed with autism was observed over ten sessions involving structured adaptive activities such as zig-zag walking and ball throwing. The results demonstrated a progressive improvement in gross motor ability, with performance increasing from 32% in the initial baseline to 70–88% during intervention and stabilizing at 93–99% in the final phase. The urgency of this research lies in addressing the motor development gap in inclusive education frameworks. The novelty of the study is rooted in its integration of play-based therapeutic strategies within an individualized, behaviorally tracked experimental model. The findings contribute significantly to adaptive physical education by validating low-cost, engaging, and personalized interventions, supporting both pedagogical practices and therapeutic programming in special education and community rehabilitation settings.